Bacterioplankton dynamics in the Southern Benguela upwelling region - Painting, Suzanne Jane (University of Cape Town, 2017)
The role of heterotrophic bacteria in the carbon and nitrogen flux of the pelagic food web was investigated during laboratory and field-based studies of the temporal development of the planktonic community after upwelling. Bacterial community structure, activity and production were closely coupled to the upwelling cycle and to the dynamics of the phytoplankton community. The initial bacterial population (<l x 10⁶ cells ml⁻¹, 20 to 40 μg C l⁻¹) was metabolically dormant. Increased availability of phytosynthetically produced dissolved organic carbon (PDOC) stimulated bacterial growth (0.016 h⁻¹) and abundance (8 to 10 x 10⁶ cells ml⁻¹, 140 to 200 μg C l⁻¹). Rapid successions in the dominant plateable strains were attributed to substrate preferences and substrate availability. Significant correlations of bacterial biomass with total standing stocks of phytoplankton and particulate carbon provided evidence of close coupling between bacteria and PDOC, and between bacteria and recalcitrant substrates available during phytoplankton decay. These relationships were best described by power functions, suggesting that bacterial biomass was relatively reduced at high levels by predation. A microcosm study indicated that zooflagellate predation could control bacterial biomass. Low net growth yields (34 to 36%) of flagellates suggested inefficient transfer of carbon to higher trophic levels, but considerable nitrogen regeneration (ca 6 to 7 μg N mg dry weight⁻¹ h⁻¹). Thymidine-measured bacterial production (TTI, <0.1 to 1.25 mg C m⁻³ h⁻¹) was linearly related to phytoplankton growth. Non-uniform response of bacteria to added tracer substrates may result in underestimates of bacterial production by 2 to 34 times by TTI, particularly in deep or oligotrophic waters, or during phytoplankton decay. Close coupling of copepod (Calanoides carinatus) production to the upwelling cycle suggested co-existence of the microbial food web and the classical diatom-copepod food chain. Recently upwelled water was dominated by phytoplankton. Assuming that all phytoplankton carbon was available for utilisation, copepods and bacteria were calculated to consume approximately 12 and 22% of primary production respectively. As the bloom declined the planktonic community was increasingly dominated by bacteria, detritus and mesozooplankton. On average, copepods consumed 60% of primary production, while bacteria consumed 49%. Carbon consumption requirements of both bacteria and copepods were satisfied by resource partitioning and carbon cycling. Under food-limiting conditions herbivorous copepods may switch to omnivory, ingesting microzooplankton of the microbial food web, and stimulating enhanced remineralisation to further sustain primary production. A generic size-based simulation model of the dynamics of the plankton community indicated that bacteria and the microbial food web increase the overall productivity of the planktonic food web, and that heterotroph predation in the smaller size classes (<200 μm) is an important mechanism in nutrient recycling.